Economic Freedom and the Process of Economic Growth: An Empirical Analysis Based on a New Measure - Judit Kapás; Pál Czeglédi (Competitio, 2010)
This paper, relying on a conceptualization of economic freedom in terms of kinds of government actions, develops a new measure of economic freedom. However, this is not art for art’s sake; instead, it allows us to provide an explanation for how particular institutions of economic freedom enhance economic development, a view upon which scholars agree. We develop two concepts related to economic freedom, namely the freedom-compatible and freedom-non-compatible institutions and use them as tools in an analysis of the process of economic growth, especially the relationship between economic freedom and long-run income. The major argument is that freedom-compatible institutions are primary determinants of income, while freedom-non-compatible institutions depend upon them and are partly the outcomes of the growth process itself, a fact which is explained by the Misesian theory of interventionism. Our regression analyses support our theoretical insights.